Does personalized information improve health plan choices when individuals are distracted? - Cornel Kaumann; Tobias Müller; Andreas Hefti; Stefan Boes (University of Bern, Department of Economics, 2018)
Choice-based health insurance systems allow individuals to select a health plan that fits their needs. However, bounded rationality and limited attention may lead to sub-optimal insurance coverage and higher-than-expected out-of-pocket payments. In this paper, we study the impact of providing personalized information on health plan choices in a laboratory experiment. We seek to more closely mimic real-life choices by randomly providing an incentivized distraction to some individuals. We find that providing personalized information significantly improves health plan choices. The positive effect is even larger and longer-lasting if individuals are distracted from their original task. In addition to providing decision support, receiving personalized information restores the awareness of the choice setting to a level comparable to the case without distraction thus reducing inertia. Our results indicate that increasing transparency of the health insurance system and providing tailored information can help individuals to make better choices and reduce their out-of-pocket expenditures.
Keywords: I13; D83; C91; 330; health insurance choice; decision under uncertainty; limited attention; information; laboratory experiment